2020
DOI: 10.1177/2150135120907372
|View full text |Cite
|
Sign up to set email alerts
|

Efforts to Reduce Infections in Delayed Sternal Closure Patients: A Survey of Pediatric Practice

Abstract: Background: Pediatric patients with sternum left open after cardiac surgery experience a higher risk for sternal wound infection (SWI). These infections are costly for programs, payers, and patients and their families. Despite efforts by individual programs to reduce infections in patients undergoing delayed sternal closure (DSC), there are no established guidelines that address preventive procedures. The purpose of this study was to determine the practice of pediatric cardiac surgery programs to prevent infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Other limitations of the current study include inconsistent data collection related to the timing of infections, dressing types, and other bedside practices and procedures that may influence infections rates in the setting of DSC. 43 The number of additional procedures such as chest explorations and washouts has been associated with infection risk in patients undergoing DSC, 6 but this information was generally unavailable in the included studies. Reason for DSC was also rarely captured by the individual studies.…”
Section: Commentmentioning
confidence: 99%
“…Other limitations of the current study include inconsistent data collection related to the timing of infections, dressing types, and other bedside practices and procedures that may influence infections rates in the setting of DSC. 43 The number of additional procedures such as chest explorations and washouts has been associated with infection risk in patients undergoing DSC, 6 but this information was generally unavailable in the included studies. Reason for DSC was also rarely captured by the individual studies.…”
Section: Commentmentioning
confidence: 99%
“…Another recent study investigated the incidence of superficial SSIs in children who underwent cardiac surgery with delayed sternal closure (DSC), a surgical strategy which is frequently used in children to prevent post-surgical complications [ 23 ]. This study reported a 2.4% superficial SSI rate in the study cohort, with a statistically significant difference between those patients who underwent DSC (6.3%) and those who did not (1.9%).…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…This study reported a 2.4% superficial SSI rate in the study cohort, with a statistically significant difference between those patients who underwent DSC (6.3%) and those who did not (1.9%). The same study also evaluated the different outcomes in terms of SSI rates among patients whose surgical wounds were medicated with wet to dry dressings and patients whose surgical wounds were medicated using negative pressure dressings: the result showed a nearly statistically significant difference ( p = 0.054), as negative pressure dressings were associated with a lower surgical site infection risk (6.4 vs. 15.7%) [ 23 ].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation